2012
DOI: 10.1097/jac.0b013e31822cbd7c
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Chronic Disease Patient Navigation in an Urban Primary Care Practice

Abstract: The purpose of this study was to evaluate the feasibility of incorporating chronic disease navigation using lay health care workers trained in motivational interviewing (MI) into an existing mammography navigation program. Primary-care patient navigators implemented MI-based telephone conversations around mammography, smoking, depression, and obesity. We conducted a small-scale demonstration, using mixed methods to assess patient outcomes and provider satisfaction. One hundred nine patients participated. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…14,15,28 tk; 3The results of our study corroborate previous findings and demonstrate that glycemic control and patient self-efficacy levels improved among patients after participating in telephone-based patient navigation. The observed effects of a 0.6% change in HbA 1c were comparable with those reported in meta-analyses and systematic reviews of pharmaceutical agents for treating diabetes and is considered to be clinically significant.…”
Section: Discussionsupporting
confidence: 81%
“…14,15,28 tk; 3The results of our study corroborate previous findings and demonstrate that glycemic control and patient self-efficacy levels improved among patients after participating in telephone-based patient navigation. The observed effects of a 0.6% change in HbA 1c were comparable with those reported in meta-analyses and systematic reviews of pharmaceutical agents for treating diabetes and is considered to be clinically significant.…”
Section: Discussionsupporting
confidence: 81%
“…We found that 34% of the navigated women could not be reached by phone. Prior studies have demonstrated similar challenges with urban safety-net populations (Battaglia et al, 2012b;Lasser et al, 2009;Myers et al, 2008;Phillips et al, 2010). Alternative protocols that use in-person outreach efforts, such as home visits and community educational sessions, may have more success (Percac-Lima et al, 2011) but are more resource-intensive.…”
Section: Discussionmentioning
confidence: 88%
“…We evaluated the following feasibility metrics: (1) practicality (ability to carry out the intervention), (2) effectiveness (ability of the intervention to increase mammography screening rates), and (3) acceptability (resident satisfaction with the intervention) (Battaglia et al, 2012b;Bowen et al, 2009). The BMC institutional review board approved this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations